2020
DOI: 10.1101/2020.04.24.20078782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Laboratory Parameters Associated with Severe or Critical Novel Coronavirus Disease 2019 (COVID-19): A Systematic Review and Meta-analysis

Abstract: Background: To date, several clinical laboratory parameters associated with COVID-19 severity have been reported. However, these parameters have not been observed consistently across studies. The aim of this review was to assess clinical laboratory parameters which may serve as markers or predictors of severe or critical COVID-19 disease Methods: We conducted a systematic search of MEDLINE, Embase, Web of Science, CINAHL and Google Scholar databases from 2019 through April 18, 2020, and reviewed bibliographies… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 63 publications
(29 reference statements)
4
26
0
Order By: Relevance
“…We registered our study protocol with the International Prospective Register of Systematic Reviews (PROSPERO); registration number CRD42020176651 [ 17 ]. This review and meta-analysis was conducted and has been reported according to The Preferred Reporting Items for Systematic Reviews and Meta- Analyses (PRISMA) statement and Meta-analysis of Observational Studies in Epidemiology (MOOSE) guidelines [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…We registered our study protocol with the International Prospective Register of Systematic Reviews (PROSPERO); registration number CRD42020176651 [ 17 ]. This review and meta-analysis was conducted and has been reported according to The Preferred Reporting Items for Systematic Reviews and Meta- Analyses (PRISMA) statement and Meta-analysis of Observational Studies in Epidemiology (MOOSE) guidelines [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additional sensitivity analyses were performed by excluding studies with a high risk of bias and studies with confidence intervals not overlapping with the 95% CIs of the pooled estimates (ie, "outlier studies"). 11 To account for Type I error rate for multiple hypothesis testing (ie, 27 and 23 laboratory markers for disease severity and mortality, respectively), Bonferroni correction was used to declare the significance levels of P values. 24 The Bonferroni corrected P value for the disease severity tests including overall estimates, sensitivity analysis by the risk of duplicates, and sensitivity analysis by the risk of bias was .002 (ie, corrected P = .05/27) and for sensitivity analysis of outliers, where only 15 laboratory markers were tested, was .003 (ie, corrected P = .05/15).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…[7][8][9] These disease processes can be monitored using various biochemical and hematologic markers that are routinely measured at the time of hospitalization, potentially contributing to the accurate prediction of severity and mortality among patients hospitalized for COVID-19 and allowing for early intervention. 10,11 However, the development of useful predictive tools incorporating laboratory parameters will require studies with large sample sizes covering broad population groups to be accurate and generalizable. Usually, individual studies are small and hence meta-analyses could provide critical evidence needed for clinical and policy decisions.…”
mentioning
confidence: 99%
See 2 more Smart Citations